DaPeCa‐1: diagnostic accuracy of sentinel lymph node biopsy in 222 patients with penile cancer at four tertiary referral centres – a national study from Denmark. (11th May 2015) - Jakobsen, Jakob K.; Krarup, Kim P.; Sommer, Peter; Nerstrøm, Henrik; Bakholdt, Vivi; Sørensen, Jens A.; Olsen, Kasper Ø.; Kromann‐Andersen, Bjarne; Toft, Birgitte G.; Høyer, Søren; Bouchelouche, Kirsten; Jensen, Jørgen B.
Abstract : Objectives: To estimate the diagnostic accuracy of sentinel lymph node biopsy (SNB) in patients with penile cancer and assess SNB complications in a national multicentre setting. Patients and methods: Retrospectively data were collected from records in four university centres by one medical doctor covering all SNBs performed in Denmark between 1 January 2000 and 31 December 2010. Patients had either impalpable lymph nodes (LNs) in one or both groins, or had a palpable inguinal mass from which aspiration cytology failed to reveal malignancy. Patients were injected with nanocolloid technetium and had a scintigram recorded before the SNB. The primary endpoint was LN recurrence on follow‐up. The secondary endpoint was complications after SNB. Diagnostic accuracy was computed. Results: In all, 409 groins in 222 patients were examined by SNB. The median (interquartile range) follow‐up of patients who survived was 6.6 (5–10) years. Of 343 negative groins, eight were false negatives. The sensitivity was 89.2% (95% confidence interval 79.8–95.2%) per groin. Interestingly, four of 67 T1G1 patients had a positive SNB. In all, 28 of 222 (13%) patients had complications of Clavien‐Dindo grade I–IIIa. Conclusion: Penile cancer SNB with a close follow‐up stages LN involvement reliably and has few complications in a national multicentre setting. Inguinal LN dissection was avoided in 76% of patients.